Public health challenges during the COVID-19 outbreak in Nepal: a commentary. Issue 4 (4th June 2020) - Sharma, Sharmistha; Bhatta, Jeevan
Abstract : Purpose: The purpose of this paper is to depict the current scenario of coronavirus diseases 2019 (COVID-19) in Nepal, how the government is tackling this pandemic as well as look at the public health challenges that Nepal is facing and might face in the future. Design/methodology/approach: This paper is a viewpoint of COVID-19 activities conducted in Nepal. Findings: Nepal is vulnerable to COVID-19, as it shares borders with China and India. Cases have started to be seen in different parts of Nepal. Government of Nepal has started various measures to control the spread of the virus such as deploying health workers, information sharing via different mediums. However, there are still many challenges that the government and public health officials need to be concerned about as well. Originality/value: This paper provides information about the situation of COVID-19 in Nepal, how the government is handling, and public health challenges that may arise. This paper can be beneficial for further public health interventions.